A survey of Onchocerca fasciata infection in camels (Camelus bactrianus) with notes on morphology - Yu, Zhi-Chao (PLoS One, 2019)
The goal of this study was to provide insight into the pathogenicity of Onchocerca fasciata in Camelus bactrianus to help control onchocerciasis. From November 2015 to January 2016, the prevalence and severity of onchocerciasis were recorded in 152 camels. Nodules containing Onchocerca were collected and observed. Adult parasites were extracted from the nodules and identified via light microscopy as well as by partial sequencing of the cytochrome oxidase subunit I (COI) gene. The sequences were examined and compared to similar sequences from other Onchocerca species. In total, 80.3% of camels were parasitized. The severity of infection varied, as camels harboured between one and fifteen nodules. The morphology and the cuticle differed in both sexes and displayed considerable variation in the thickness and structure of different body parts. Identification was further confirmed using molecular biology methods. This study provides a comprehensive morphological description of Onchocerca fasciata isolated from camels. The prevalence and intensity of infection (assessed via nodules) varied in the Bactrian camels. The structure of the cuticle was an important morphological feature for species differentiation in Onchocerca. Based on our data, the morphological assessment of O. fasciata represents a reliable method to characterize other Onchocerca species.